The Combination of Culture and Art in Muludan Mask Dance as a Strategy for Preserving Tradition: Muludan Mask tradition as a component of Surabaya's place identity - Santiana, Anindra Candrika; Riyanto, Edi Dwi; Afdholy, Nadya (Talenta Publisher, 2024)
Festivals and celebrations are among many ways for a culture or tradition to be presented to society. Muludan Mask is a Surabaya culture where children often play with these masks when celebrating the Prophet’s Birthday. But unfortunately, this culture is starting to be eroded by the times along with the development of the globalization era. Many efforts have been made by both the Surabaya government and communities in Surabaya to preserve the Muludan mask tradition. One of the efforts made by the Arbaya Dance Community in 2017 and 2018 was to celebrate the Prophet's birthday at Balai Pemuda Surabaya by dancing the Muludan Mask dance together. The qualitative method with interviews as a data collection method was applied to collect data from within the Arbaya Dance Community as the source to determine how effective and sustainable the efforts to preserve the Muludan mask tradition are. This article wants to show how art and culture are combined to preserve a tradition since tradition is one of the components composing a place identity. The results of this research show that the existence of the Muludan Mask tradition needs to be reaffirmed so that it doesn’t fade completely from Surabaya society because it can affect the identity of Surabaya. This tradition's small number of cultural practitioners causes this article to have only one source from one community. It is hoped that this article can provide further information about the Muludan Mask and help this tradition to be noticed by the Surabaya people.